A VECM Approach to Explain Dynamic Alliance Between Stock Markets - Nautiyal, Neeraj; Kavidayal, P. C. (Indian Journal of Finance, 2018)
This paper attempted to examine the extent of cross - country returns and comovement between the stock markets of six developed benchmark countries (USA, UK, Japan, Germany, France, and Hong Kong) and five emerging benchmark countries (Russia, India, China, Malaysia, and Korea). The study analyzed time series data between the periods from April 2006 to March 2016. This paper used time-series vector error correction model approach of stationarity test and cointegration test to establish long-run and short-run relationship between emerging and developed economies. To assess the stability of the relationship (response to shock) amongst the variables over time, forecast error variance decomposition was used. The empirical results suggested that short-run causality primarily ran from the Hong Kong market to India and from India to Malaysia, Germany to Korea, and also from France to China. The findings of the study showed that the speed of adjustment in the vector error correction model was significant but relatively slow. The variance decomposition analysis confirmed the short and long-run stock market linkage between the sample countries. Therefore, it was inferred that stock market integration and causation between different markets and indices had changed.